2020
DOI: 10.1038/s41389-020-00272-0
|View full text |Cite
|
Sign up to set email alerts
|

WAVE3 phosphorylation regulates the interplay between PI3K, TGF-β, and EGF signaling pathways in breast cancer

Abstract: Both TGF-β and the PI3K-AKT signaling pathways are known activators of various intracellular pathways that regulate critical cellular functions, including cancer cell survival and proliferation. The interplay between these two oncogenic pathways plays a major role in promoting the initiation, growth, and progression of tumors, including breast cancers. The molecular underpinning of the inter-relationship between these pathways is, however, not fully understood, as is the role of WAVE3 phosphorylation in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 50 publications
6
27
0
Order By: Relevance
“…Our published studies have also shown that phosphorylation of WAVE3 at four tyrosine residues (Fig. 1 A) can be achieved upon stimulation with PDGF and activation of phosphatidylinositol 3-kinase (PI3K) signaling pathway 15 , 16 . Furthermore, we have also shown that the PRD domain of WAVE3 is required for the oncogenic activity of WAVE3 by activating the CSC phenotype in TNBC cells 14 .…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…Our published studies have also shown that phosphorylation of WAVE3 at four tyrosine residues (Fig. 1 A) can be achieved upon stimulation with PDGF and activation of phosphatidylinositol 3-kinase (PI3K) signaling pathway 15 , 16 . Furthermore, we have also shown that the PRD domain of WAVE3 is required for the oncogenic activity of WAVE3 by activating the CSC phenotype in TNBC cells 14 .…”
Section: Resultsmentioning
confidence: 82%
“…We used STR DNA fingerprinting analysis for regular authentication of cells that we used for this study. WAVE3-deficient (WAVE3-KO) cells were produced using lentiviral transduction as described 14 , 15 . For each BC cell line, we used two different and verified WAVE3-specific sgRNAs and a scrambled sgRNA i.e., nonsilencing sgRNA 14 , 15 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations